2014
DOI: 10.1186/1550-2783-11-17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbohydrate combined with caffeine on repeated sprint cycling and agility performance in female athletes

Abstract: BackgroundCaffeine (CAF) has been shown to improve performance during early phase of repeated sprint exercise; however some studies show that CAF also increases the magnitude of physical stress represented by augmented blood lactate, glucose, and cortisol concentrations during latter phase of repeated sprint exercise. No studies have investigated the efficacy of combined carbohydrate (CHO) and CAF consumption during repeated sprint exercise (RSE) in female athletes. Thus, the purpose of this study was to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 58 publications
(101 reference statements)
1
35
1
8
Order By: Relevance
“…A reduction in cortisol levels by 16 % and increased level of testosterone by 37 % was noted. Authors suggest that the observed improvement may support sports performance [82,83].…”
Section: Dietary Supplementsmentioning
confidence: 94%
See 1 more Smart Citation
“…A reduction in cortisol levels by 16 % and increased level of testosterone by 37 % was noted. Authors suggest that the observed improvement may support sports performance [82,83].…”
Section: Dietary Supplementsmentioning
confidence: 94%
“…The studies concerning consumption of drinks containing carbohydrates and caffeine during workout have shown that the highest increase in cortisol levels were achieved in the group that supplemented caffeine without carbohydrates [81,82].…”
Section: Dietary Supplementsmentioning
confidence: 99%
“…However, other studies have not shown significant improvement with caffeine. In a study with 11 female athletes performing repeated sprint cycling, neither ingestion of caffeine plus placebo nor caffeine plus carbohydrate improved repeated sprint performance with short rest intervals [71]. Many athletes use caffeine to counter sleep deprivation, but a study on semiprofessional tennis players showed that caffeine did not make up for lost sleep with regard to serving accuracy [72].…”
Section: Performancementioning
confidence: 98%
“…This hypothesis has been tested and is well supported in studies using male subjects (6); however, the data among female participants are sparse. To date, there are limited investigations evaluating the effects of caffeine supplementation on changes in muscular parameters among women (47,76,80,85,90). Of those studies, beneficial results from caffeine supplementation are equivocal.…”
Section: Introductionmentioning
confidence: 99%
“…When observing changes in highintensity cycling performance, caffeine has been ineffective when supplemented in women (76,80,90). Early evidence investigating the effects of caffeine on high-intensity cycling time to exhaustion revealed no differences with small (4 mg/kg), medium (7 mg/kg), or high (10 mg/kg) dosing protocols (90).…”
Section: Introductionmentioning
confidence: 99%